2014
DOI: 10.1002/hipo.22286
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the effects of histone deacetylase inhibitors on hippocampal memory and cognitive aging

Abstract: Converging results link histone acetylation dynamics to hippocampus-dependent memory, including evidence that histone deacetylase inhibitor (HDACi) administration enhances long-term memory. Previously we demonstrated that aging disrupts the coordinated epigenetic response to recent experience observed in the young adult hippocampus. Here we extended that work to test the cognitive effects of a novel, brain-penetrant HDACi (EVX001688; EVX) that we confirmed yields robust, relatively long lasting dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…However, we do not expect morphometric differences to significantly affect results, since metabolite ratios (relative to Cr) are relatively insensitive to voxel composition (particularly CSF contamination). Finally, no significant changes were observed in the hippocampus in this study, despite the well-known importance of this structure for memory and other age-related cognitive dysfunction 40, 54, 55 . Lack of significant findings may be in part due to the generally lower spectral quality obtained in this region due to magnetic susceptibility effects from bone/air/tissue interfaces proximal to the anterior temporal lobe, as well as partial volume with surrounding tissue due to the small size of the hippocampus.…”
Section: Discussioncontrasting
confidence: 77%
“…However, we do not expect morphometric differences to significantly affect results, since metabolite ratios (relative to Cr) are relatively insensitive to voxel composition (particularly CSF contamination). Finally, no significant changes were observed in the hippocampus in this study, despite the well-known importance of this structure for memory and other age-related cognitive dysfunction 40, 54, 55 . Lack of significant findings may be in part due to the generally lower spectral quality obtained in this region due to magnetic susceptibility effects from bone/air/tissue interfaces proximal to the anterior temporal lobe, as well as partial volume with surrounding tissue due to the small size of the hippocampus.…”
Section: Discussioncontrasting
confidence: 77%
“…Consistently, treatment with TSA, SAHA, or CI-994 either reduced the threshold for LTP induction or increased the magnitude of potentiation in the hippocampus and amygdala (17,19,24,27,30,32), although these effects were not always observed (33). Furthermore, multiple HDAC inhibitors improved performance in fear conditioning, object location, novel object recognition, food preference, and spatial memory tasks (24-27, 29-32, 34-38), again with some exceptions (19,33,39,40). Thus, endogenous HDAC activity clearly plays a critical role in cognitive performance and appears to normally restrain both structural and functional synaptic plasticity.…”
Section: Hdac Inhibitors and Memory Enhancementmentioning
confidence: 78%
“…For example, Castellano et al (2014) reported that 24-h retention of fear memory is unaffected in young rats provided pretraining injection of a potent, brain penetrant HDAC inhibitor (i.e., EVX001688, FORUM Pharmaceuticals) that they directly confirmed yields robust increases in hippocampal histone acetylation at the time of fear conditioning. Negative results were also obtained with the more commonly used HDAC inhibitor, sodium butyrate, and indeed in this case there was a clear trend toward impaired memory with treatment.…”
Section: Hdacs As Pharmacological Targets For Memory Enhancementmentioning
confidence: 99%
“…Castellano et al (2014), Epigenetic contributions to cognitive aging www.learnmem.org for example, reported that, rather than uniformly increasing histone H3 and H4 acetylation, behavioral training in multiple animal models, including strains and testing procedures adopted from earlier work (Levenson et al 2004;Peleg et al 2010), led to modest decreases or no change in hippocampal histone acetylation. Indeed other work from the same group suggests that bidirectional and subregion-specific regulation of experience-dependent histone acetylation might contribute to the different pattern of results observed across studies (Castellano et al 2012).…”
Section: Hdacs As Pharmacological Targets For Memory Enhancementmentioning
confidence: 99%
See 1 more Smart Citation